Study of metabolic syndrome in patients of Vitiligo: A single-center observational study - Gourh, Vishal; Anita Arya,; Anand Dubey,; Simmi Dube, (Asian Journal of Medical Sciences, 2022)
Background: Metabolic syndrome (MetS) has been observed in patients with vitiligo. Literature suggests that there is some link between vitiligo and MetS. Autoimmunity, oxidative stress, and decreased number of melanocytes are involved in its pathogenesis. Aims and Objectives: This study aimed to assess MetS in patients of vitiligo, its association with different types of vitiligo, age of patients, and duration of vitiligo. Materials and Methods: We enrolled 62 vitiligo patients who met inclusion criteria in this cross-sectional study from August 1, 2020 to July 31, 2021. Detailed history, physical examination, and blood investigations were done in all patients and NCEP ATP III criteria were used for diagnosis of MetS. Results: Mean age of participants was 35.98±15.48 years; M: F: was 1:2.3. MetS was observed in 12.9% vitiligo patients. Advancing age and non-segmental vitiligo were significantly associated with MetS (P<0.05). Conclusion: Vitiligo is a condition which may affect individual at any age and carries risk of developing MetS in the future. In our study, MetS is observed in 12.9% patients with vitiligo. Early identification of MetS and appropriate management of such patients may help in reducing cardiovascular morbidity and mortality. Further prospective studies required to establish relation between vitiligo and MetS.